University Governance
VIII, 322 p.
Keywords: This book deals with change processes in higher education systems in seven countries and explores which public policies have been chosen, and which organizational designs and steering tools have been implemented. Doctoral education and research budgets are studied in depth. To what extent do national specificities survive, and to what extent does European convergence occur? All seven countries tend to turn universities into rationalized organizations linking multiple heterogeneous stakeholders and clarifying their training and research missions. They also reform methods used by public authorities to steer at a distance by way of performance evaluation and incentive approaches. This book suggests that grand narratives such as NPM and Network Governance narratives do not tell the history of change. They may influence visions and tools developed by reformers, but policymaking and its implementation remain dependent on specific national settings.